Integrated Adaptation Tipping Points (IATPs) for urban flood resilience. (October 2018) - Ahmed, Farhana; Khan, M Shah Alam; Warner, Jeroen; Moors, Eddy; Terwisscha Van Scheltinga, Catharien
This paper applies an Adaptation Tipping Point (ATP) approach for the assessment of vulnerability to flooding in the city of Dhaka, Bangladesh. A series of rigorous modelling exercises for fluvial and pluvial flooding was conducted to identify the critical ATPs of the physical system, under both existing and proposed flood risk management strategies, for different urban and climate change scenarios. But a standalone assessment of the physical system's ATPs is insufficient to gain a complete understanding of flood risks; community resilience also depends on people's adaptability and the acceptance of risks by the community in question. Through participatory public consultations, this study determines the critical ATPs for community risk acceptance. The concept of the "Integrated Adaptation Tipping Point (IATP)", introduced here, combines the accepted level of risk to the community with the ATPs for physical systems. This approach reveals that the assessed vulnerability to flooding increases when social tipping points are considered.